Moisture Dependent Physical and Thermal Properties of Coleus Tubers - Chandrasekar, V.; Kailappan, R.; Kasthuri, R.; Rajamani, K (Journal of Agricultural Engineering, 2013)
Some important physical and thermal properties of coleus tubers were determined in the moisture range of 466.62 to 21.52% (d.b). Selected physical properties, namely weight, size; bulk density, particle density and porosity increased with increase in moisture content. Specific heat and thermal conductivity increased with increase in moisture content, while thermal diffusivity recorded a decreasing trend with increase in moisture content.